Suppressing Tau Aggregation and Toxicity by an Anti-Aggregant Tau Fragment - Pir, Ghulam Jeelani (Mol Neurobiol, 2018)
Tau aggregation is a hallmark of a group of neurodegenerative diseases termed Tauopathies. Reduction of aggregation-prone Tau has emerged as a promising therapeutic approach. Here, we show that an anti-aggregant Tau fragment (F3(ΔKPP), residues 258–360) harboring the ΔK280 mutation and two proline substitutions (I(277)P & I(308)P) in the repeat domain can inhibit aggregation of Tau constructs in vitro, in cultured cells and in vivo in a Caenorhabditis elegans model of Tau aggregation. The Tau fragment reduced Tau-dependent cytotoxicity in a N2a cell model, suppressed the Tau-mediated neuronal dysfunction and ameliorated the defective locomotion in C. elegans. In vitro the fragment competes with full-length Tau for polyanionic aggregation inducers and thus inhibits Tau aggregation. Our combined in vitro and in vivo results suggest that the anti-aggregant Tau fragment may potentially be used to address the consequences of Tau aggregation in Tauopathies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12035-018-1326-z) contains supplementary material, which is available to authorized users.